2006 International Conference on Field Programmable Logic and Applications 2006
DOI: 10.1109/fpl.2006.311225
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Bit Carry Chains for High-Performance Reconfigurable Fabrics

Abstract: Ripple-carry architectures are the norm in today's reconfigurable fabrics. They are simple, require minimal routing, and are easily formed across arbitrary cells in a fabric. However, their computation delay grows linearly with operand width. Many different fabric carry-chains have been presented in literature offering non-linear delays, but generally require a significant investment in routing and processing area. Carry-skip chains are well-known in arithmetic logic design, and although they too possess a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This would require a large manual effort to design each individual cell at the transistor level, and would complicate the layout process for the entire chip. Frederick and Somani [2006] proposed a uniform logic block with carry chains that could efficiently implement a carry-skip adder; a similar bidirectional carry-skip chain was earlier proposed by Cherepacha and Lewis [1996, Figure 6]. Kaviani et al [1998] and Leijten-Nowak and Van Meerbergen [2003] developed ALU-like blocks that support arithmetic functions such as addition, subtraction and (partial) multiplication.…”
Section: Fpga Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…This would require a large manual effort to design each individual cell at the transistor level, and would complicate the layout process for the entire chip. Frederick and Somani [2006] proposed a uniform logic block with carry chains that could efficiently implement a carry-skip adder; a similar bidirectional carry-skip chain was earlier proposed by Cherepacha and Lewis [1996, Figure 6]. Kaviani et al [1998] and Leijten-Nowak and Van Meerbergen [2003] developed ALU-like blocks that support arithmetic functions such as addition, subtraction and (partial) multiplication.…”
Section: Fpga Architecturementioning
confidence: 99%
“…The logic clusters of the Altera Stratix II-IV and Xilinx Virtex-5 FPGAs can be configured to implement ternary (3-input) addition using fast carry chains [Cherepacha and Lewis 1996;Hauck et al 2000;Frederick and Somani 2006]. The primary advantage of the carry chains is that the carry bits are propagated directly from one cell to its adjacent neighbor, thereby avoiding the overhead of the routing network.…”
Section: Introductionmentioning
confidence: 99%
“…This would require a large manual effort to design each individual cell at the transistor level, and would complicate the layout process for the entire chip. Frederick and Somani [12] proposed a uniform logic block with carry-chains that could efficiently implement a carry-skip adder; a similar bi-directional carry-skip chain was earlier proposed by Cherepacha and Lewis [8, Fig. 6].…”
Section: Fpga Architecturementioning
confidence: 99%
“…Kuon and Rose [19] have recently shown that hard, hand-optimized IP cores-namely DSP and MAC blocks-do not offer tangible performance advantages due to the high cost of routing data to and from these blocks, and mismatches in bitwidth. Previous enhancements to FPGA logic blocks, such as support for binary and ternary addition [1,3,40,41] and carry-chains [8,12,14,18,21], have improved FPGA performance for arithmetic operations. Nonetheless, the performance gap between ASICs and FPGAs remains.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of carry chains that have been proposed are for different types of adders [8,14,17,18,19]; the carry chains on commercial FPGAs available from Xilinx and Altera also fall into this category. One interesting alternative is a carry chain that allows an Altera-style logic cell to be configured as a 7:2 compressor, which is used for multi-operand addition [20].…”
Section: Related Workmentioning
confidence: 99%